A Combined Approach of High-Frequency rTMS and Food-Inhibition Association Training Reduces Chocolate Snack Consumption - Ahn, Hyeon Min; Ham, Byung-Joo; Kim, Sang Hee (Frontiers in Psychiatry, 2019)
The ability to control impulsive urges is important for maintaining healthy eating habits. Various training strategies have been developed to reduce impulsive urges for food and strengthen cognitive control over tempting food intake. One frequent strategy uses food-inhibition association to alter the associative process between food cues and impulsive urges. Another strategy, repetitive transcranial magnetic stimulation (rTMS) over the dorsolateral prefrontal cortex (DLPFC) to strengthen cognitive control, has received increased attention. Findings, so far, are mixed and limited due to small effect size, interpretational ambiguity, and lack of standardized brain stimulation parameters. We examined whether tempting chocolate snack intake is modulated by food-inhibition association training combined with high-frequency rTMS. In Experiment 1, healthy young adult female volunteers (body mass index [BMI] range, 17-27) performed a food go/no-go task in which chocolate images were consistently paired with either a no-go cue (no-go group, n = 14) or a go cue (go group, n = 14), or both go and no-go cues at equal frequencies (neutral group, n = 15). In Experiment 2, we examined the effect of combined treatment with high-frequency rTMS and food go/no-go training. Sixty healthy young adult female volunteers (BMI range, 15-31) were randomly assigned to one of four groups with equal numbers of participants: rTMS/no-go, rTMS/neutral, sham/no-go, or sham/neutral. rTMS or sham stimulation was applied over the left DLPFC prior to the food go/no-go training task. After training, in both experiments, a taste test was conducted, and the amount of snack intake was measured. In Experiment 1, the no-go training group consumed fewer chocolate snacks than the go training group. No difference was found between the no-go and neutral training groups. In Experiment 2, combined rTMS and no-go training effectively reduced chocolate snack intake compared with neutral training. Although limited by the small sample size, our results suggest the therapeutic potential of combined high-frequency rTMS and food-inhibition association training in enhancing control over the intake of tempting foods in individuals with overeating.